Original paperApprehension of the disease by patients suffering from psoriasis - Reich, Adam; Welz-Kubia, Kalina; Rams, Łukasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Psoriasis affects about 1–2% of the entire population. Due to its chronicity and relapsing course, psoriasis has a great influence on patients’ quality of life and psychological status. Aim: To evaluate apprehensaion of the disease by psoriatic patients. Material and methods : One hundred psoriasis patients (36 females, 64 males; mean age 47.3 ±15.8 years) were enrolled. Mean psoriasis severity assessed according to PASI was 17.1 ±10.0 points. Each participant underwent a careful physical examination and completed a specially designed questionnaire containing questions about perception of psoriasis severity, disease aggravating factors, most bothersome symptoms, possible causes of psoriasis and treatment efficacy. Results : A correlation between patients’ psoriasis assessment and objective measurement of disease intensity by PASI was weak, albeit significant (ρ = 0.37, p < 0.001). A total of 49% of patients indicated that psoriasis had an enormous negative impact on their life and 40% declared that psoriasis decreased their self-esteem. Patients with decreased self-esteem were significantly younger and more frequently employed. A marked portion of patients believed that their disease will be cured in the future. Patients expecting a rapid cure of disease had experienced a later disease onset and suffered from psoriasis significantly shorter. The most burdensome symptoms of psoriasis were intense epidermal scaling (66% of responders), itching (65%), skin redness (51%), burning (44%), dandruff (38%), and nail abnormalities (37%). Conclusions : Psoriasis may negatively affect patients’ everyday life, but the degree of that influence and the level of psoriasis understanding depend on various clinical parameters as well as on demographic characteristics.